Projeto de controle de formação por modos deslizantes fuzzy adaptativo utilizando a estratégia líder-seguidor na resolução do problema de rastreamento de trajetória - Ramos, Thiago Rogelio (2019)
This work presents the design of an adaptive fuzzy sliding mode kinematic controller (AFSMC) integrated with the proportional plus derivative dynamic control system for formation control of mobile robots with diﬀerential drive, on which uncertainties and perturbationsoccur,withthegoaloftrackingtrajectories.Therobotsformationisbasedon theleader-followerstrategy.Stabilityanalyzesofcontrolsystemsareperformedthroughthe application of Lyapunov theory. It is necessary to consider that the sliding mode technique presents robustness to the uncertainties, nevertheless causes the eﬀect of chattering. To attenuate chattering, two techniques are used: one that replaces the discontinuous portion of the system with the application of a continuous function in the boundary layer and another based on adaptive fuzzy control. To verify the stability of the proposed control system,simulationswereperformedusingtheproposedcontrolsystemsintheidealscenario, simulated in Matlab/Simulink, and in the realistic scenario provided by the MobileSim simulator